Improving Technical and Conceptual Photography Skills of Vocational School Students: A Case Study of the "Recording Vision, Building Works" Workshop Intervention at SMKN 8 Jayapura - Tindia Febriyati; Kelana Vhisnu Nugroho (International Journal of Science and Environment (IJSE), 2026)
Vocational education in Visual Communication Design (VCD) faces challenges in bridging the school curriculum with the dynamic demands of industry 4.0. Vocational high school (SMK) students, as future creative talents, often master basic technical skills but are reported to lack conceptual depth, industry insight, and mature creative vision. This Community Service (PkM) activity aims to improve the fundamental and practical photography competencies of 32 VCD students from SMKN 8 Kota Jayapura. The method used was a two-day interactive workshop (November 10-11, 2025) with a quasi-experimental one-group pre-test/post-test design. The intervention included theory sessions (exposure triangle, composition, professional ethics) and intensive practice sessions simulated based on client briefs (model photography and product photography). Data was collected using pre-test and post-test questionnaires as well as qualitative observations. The results of the intervention showed significant effectiveness. Participants' average comprehension scores jumped from 32.58% on the pre-test to 59.73% on the post-test, representing an absolute increase of 27.15 percentage points. Detailed analysis revealed clear learning disparities: directly visualized technical-practical concepts (e.g., Aperture or 'Bokeh') experienced a dramatic increase (+55 percentage points), while professional-abstract concepts (e.g., Ethics or 'Model Release') remained challenging with the lowest final scores (23%). It is concluded that the "Capturing Vision, Building Work" workshop method is highly effective in improving technical photography skills. However, these findings highlight the need for stronger integration between professional ethics and hands-on practice in future VCD pedagogy.from each macroinvertebrate species towards environmental conditions.